Symmetry and asymmetry in certain atoms - Ravelonirina, Hanitriniaina Nina RAZAFIHARISOA; Jean Jolly RAKOTO ,; - Hanitriniaina Sammy Grégoire RAVELONIRINA , (International Journal of Applied Mathematical Research, 2024)
Symmetry and asymmetry play a crucial role in the stability of the fundamental components of matter. Thus, the main objective of this work is to study the existence of symmetry, this universal geometric property of matter, in certain atoms, in order to provide a classification of the elements of the periodic table based on a symmetry criterion.